Conflits et recomposition d'un ordre régional dans la Corne de l'Afrique - Marchal, Roland (Études internationales)

(untitled) (Institut québécois des hautes études internationales, 1991)
From 1988, there has been a change in the pace of events in the Horn of Africa. The United States and the Soviet Union opted out of the logic of cold war which obtained up to then, leaving more room open to an intervention by neighbouring States (Israel, Irak, the Gulf States). The extension into the Horn of the Middle-Eastern rivalries is all the more real since the political powers are all in a precarious position, despite their use of an unmitigated coercion. Yet, the internal dynamics, which are complex, are still prevailing. It does not seem from their current evolution that there is any hope for real peace talks to end the conflicts.